1998
DOI: 10.1128/aem.64.11.4180-4184.1998
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Aromatic Hydrocarbons in an Extremely Acidic Environment

Abstract: The potential for biodegradation of aromatic hydrocarbons was evaluated in soil samples recovered along gradients of both contaminant levels and pH values existing downstream of a long-term coal pile storage basin. pH values for areas greatly impacted by runoff from the storage basin were 2.0. Even at such a reduced pH, the indigenous microbial community was metabolically active, showing the ability to oxidize more than 40% of the parent hydrocarbons, naphthalene and toluene, to carbon dioxide and water. Treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(34 citation statements)
references
References 29 publications
0
33
0
1
Order By: Relevance
“…Interestingly, Acidiphilium sequences were also found to dominate microbial communities in a hexadecane mineralizing soil-sand mixture derived from a petroleum seep in Yellowstone Park (Hamamura et al 2005). Biodegradation of aromatic hydrocarbons under acidic conditions has previously been observed in a man-made long-term coal pile storage basin (Stapleton et al 1998). In this case, the activity of eukaryotic micro-organisms was essential for aromatic hydrocarbon degradation in the pH 2AE0 basin.…”
Section: Clonementioning
confidence: 72%
“…Interestingly, Acidiphilium sequences were also found to dominate microbial communities in a hexadecane mineralizing soil-sand mixture derived from a petroleum seep in Yellowstone Park (Hamamura et al 2005). Biodegradation of aromatic hydrocarbons under acidic conditions has previously been observed in a man-made long-term coal pile storage basin (Stapleton et al 1998). In this case, the activity of eukaryotic micro-organisms was essential for aromatic hydrocarbon degradation in the pH 2AE0 basin.…”
Section: Clonementioning
confidence: 72%
“…Acidophilic, heterotrophic Alphaproteobacteria such as Acidocella occur world-wide in natural hydrocarbon seeps, presumably utilizing the hydrocarbon as an energy and carbon source (Roling et al, 2006). Acidocella and Pichia were isolated from the same PAH-contaminated soil, in a study that concluded that an undefined consortium of yeasts, filamentous fungi and bacteria was responsible for degradation of aromatic hydrocarbons (Stapleton et al, 1998). Whether the biofilm members we have described are also able to mineralize organic pollutants in the groundwater is currently unknown.…”
Section: Discussionmentioning
confidence: 94%
“…Acidocella was originally described as inhabiting acidic aquatic habitats (Kishimoto et al, 1995) and is found as planktonic cells in acid mining lakes (Johnson et al, 2001;Wenderoth & Abraham, 2005). Pichia relatives can be recovered from acidic lakes (Gadhano & Sampaio, 2006), and Acidocella and Pichia have previously been reported as occurring together in highly acidic environments, although not as an obvious biofilm (Stapleton et al, 1998). Trichoderma asperellum has not been recorded from groundwater, but is known to grow at pH 2.2 (Kawai et al, 2000), and both Trichoderma and Candida have been recorded in sandstone, which is the bedrock type in the area (Burford et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Some PAH degraders are extremophiles, which are microorganisms that can thrive in and withstand extreme environmental conditions (Tango & Islam, 2002). Examples include Halomonas aromativorans (Garcia et al, 2005), Halomonas organivorans (Garcia et al, 2004), and Acidocella-related Strain SRS (Stapleton et al, 1998), which can metabolize salicylate. Thermus brockii (Feitkenhauer et al, 2003) and Mycobacterium sp.…”
Section: Overview Of Microbial Metabolism Of Hmw Pahsmentioning
confidence: 99%